Angiopoietin‐like 4 production upon treatment with hypoxia and L‐mimosine in periodontal fibroblasts. (20th March 2019) - Janjić, Klara; Schellner, Alwina; Engenhart, Alexander; Kernstock, Kurt; Schädl, Barbara; Moritz, Andreas; Agis, Hermann
Abstract : Background and objective: A key factor in the modulation of angiogenesis as well as in bone resorption is angiopoietin‐like 4. However, the role of angiopoietin‐like 4 in periodontal tissue is unknown. Here, we hypothesized that hypoxia and the hypoxia mimetic agent L‐mimosine can induce the production of angiopoietin‐like 4 in periodontal fibroblasts. Methods: Human periodontal ligament fibroblasts (PDLF) were cultured in monolayer and spheroid cultures. The cultures were incubated in the presence of hypoxia or L‐mimosine. Angiopoietin‐like 4 mRNA and protein levels were measured by qPCR and ELISA, respectively. Also, the impact of Lipopolysaccharides of E. coli and P. gingivalis, interleukin (IL)‐1β and tumor necrosis factor (TNF)α was evaluated. Furthermore, we tested dependency on hypoxia‐inducible factor (HIF)‐1 activity by Western blotting for HIF‐1 and inhibitor studies with echinomycin. Potential autocrine effects were assessed by exposure of PDLF to recombinant angiopoietin‐like 4 in full length, C‐terminal and N‐terminal fragments. The impact on viability, DNA synthesis, alkaline phosphatase, and matrix mineralization was evaluated. Results: Both hypoxia and L‐mimosine elevated angiopoietin‐like 4 mRNA and protein levels in monolayer cultures of PDLF. HIF‐1 was elevated after both hypoxia and L‐mimosine treatment. LPS, IL‐1β, and TNFα did not modulate angiopoietin‐like 4 levels significantly. Addition of echinomycin in the cultures inhibited the production of angiopoietin‐like 4. In spheroid cultures of PDLF, the increase did not reach the level of significance at mRNA and protein levels. Angiopoietin‐like 4 in full length, C‐terminal, and N‐terminal fragments did not modulate viability, DNA synthesis, alkaline phosphatase, and matrix mineralization. Conclusion: Overall, we found that hypoxia and the hypoxia mimetic agent L‐mimosine can stimulate angiopoietin‐like 4 production in monolayer cultures of PDLF. This increase depends on HIF‐1 activity. Future studies will reveal how the modulation of angiopoietin‐like 4 in the periodontium contributes to periodontal disease and regeneration.